The role of n-3-derived specialised pro-resolving mediators (SPMs) in microglial mitochondrial respiration and inflammation resolution in Alzheimer’s disease - Mary Slayo; Christoph Rummel; Pasindu Hansana Singhaarachchi; Martin Feldotto; Sarah J. Spencer (Molecular Neurodegeneration)
Abstract Alzheimer’s disease (AD) is the most common form of dementia globally and is characterised by reduced mitochondrial respiration and cortical deposition of amyloid-β plaques and neurofibrillary tangles comprised of hyper-phosphorylated tau. Despite its characterisation more than 110 years ago, the mechanisms by which AD develops are still unclear. Dysregulation of microglial phagocytosis of amyloid-β may play a key role. Microglia are the major innate immune cell of the central nervous system and are critical responders to pro-inflammatory states. Typically, microglia react with a short-lived inflammatory response. However, a dysregulation in the resolution of this microglial response results in the chronic release of inflammatory mediators. This prolongs the state of neuroinflammation, likely contributing to the pathogenesis of AD. In addition, the microglial specialised pro-resolving mediator (SPM) contribution to phagocytosis of amyloid-β is dysregulated in AD. SPMs are derivatives of dietary n-3 polyunsaturated fatty acids (PUFAs) and potentially represent a strategic target for protection against AD progression. However, there is little understanding of how mitochondrial respiration in microglia may be sustained long term by n-3-derived SPMs, and how this affects their clearance of amyloid-β. Here, we re-evaluate the current literature on SPMs in AD and propose that SPMs may improve phagocytosis of amyloid-β by microglia as a result of sustained mitochondrial respiration and allowing a pro-resolution response.